2007
DOI: 10.1152/ajpregu.00074.2006
|View full text |Cite
|
Sign up to set email alerts
|

Impaired defense of core temperature in aged humans during mild cold stress

Abstract: Aged humans often exhibit an impaired defense of core temperature during cold stress. However, research documenting this response has typically used small subject samples and strong cold stimuli. The purpose of this study was to determine the responses of young and older subjects, matched for anthropometric characteristics, during mild cold stress. Thirty-six young (YS; 23 +/- 1 years, range 18-30) and 46 older (OS; 71 +/- 1 years, range 65-89) subjects underwent a slow transient cold air exposure from a therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(117 citation statements)
references
References 37 publications
4
110
0
1
Order By: Relevance
“…Our study identifi ed age as a variable that interferes with cutaneous measurement, but the role of gender is less obvious. Older persons showed impaired defense (stability) of core temperatures during cold and heat stresses, and their cutaneous vascular reactivity was reduced (12,13). Use of a simple infrared thermometry, rather than sophisticated imaging, should not be considered a limitation because this method concerns the relationship between cutaneous and central core temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identifi ed age as a variable that interferes with cutaneous measurement, but the role of gender is less obvious. Older persons showed impaired defense (stability) of core temperatures during cold and heat stresses, and their cutaneous vascular reactivity was reduced (12,13). Use of a simple infrared thermometry, rather than sophisticated imaging, should not be considered a limitation because this method concerns the relationship between cutaneous and central core temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Age-dependent neural degeneration observed in thermoreceptors can reduce both physiological and perceptual thermal sensitivity. Impaired cutaneous vascular function and delays in the sweating and shivering thresholds have been reported in age comparison studies [2,3,4,5,6]. Likewise, reduced thermal sensations in older adults have been reported, alongside a number of other tactile responses (touch, pressure and noxious thermal sensitivity) [7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 91%
“…It should be noted, however, that heart rate differences persisted into subsequent work bouts in the aforementioned studies (Khomenok et al, 2008;Selkirk et al, 2004), suggesting that more than postural differences are involved. No previous studies have reported changes in skin blood flow or stroke volume changes during extremity immersion cooling; however using cold air exposure or water-perfused suit models, it is well-established that skin temperature and skin blood flow are directly related (DeGroot and Kenney, 2006;Stephens et al, 2001). Therefore, considering the reduction in heart rate reported in several studies, it is reasonable to speculate that skin blood flow requirements are reduced, peripheral pooling is reduced, and stroke volume is maintained.…”
Section: Effects On Cardiovascular Strainmentioning
confidence: 99%